Distribution of cytochemically detectable cholesterol in the electric organ of Torpedo marmorata. - Perrelet, A (1982)
A cytochemical probe for cholesterol, the polyene antibiotic filipin, was applied to aldehyde-fixed samples of the electric organ of Torpedo marmorata to identify filipin-binding sites in the various membrane components of the organ and, hence, the probable cholesterol content at these levels. In both thin-sectioned and freeze-fractured samples, filipin-cholesterol complexes appeared numerous and homogeneously distributed on the Schwann cell plasma membrane. On the presynaptic membrane, filipin-cholesterol complexes occurred in patches alternating with unlabeled membrane segments. The postsynaptic, acetylcholine receptor-rich plasma membrane of the electroplax showed no or few filipin-cholesterol complexes in the flat region and upper part of the invaginations (both areas characterized by a lattice of small intramembrane particles); however, the membrane of the bottom part of the postsynaptic invaginations contained several complexes. The ventral, noninnervated plasma membrane of the electroplax showed a moderate, homogeneous filipin labeling. These data suggest that the distribution of cholesterol among membranes of the electroplax is not homogeneous and that the acetylcholine receptor-rich region of the postsynaptic membrane (as characterized by the lattice of small intramembrane particles) may contain little cholesterol.